The National Spirit of Kiai Pesantren: An Analysis of the Ideas and Spirit of Independence of KH. Bisri Mustofa in the Interpretation of Al-Ibriz - Zainuddin, Muhadi; Makfi, Miqdam (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2019)
The idea and spirit of kiai pesantren (Islamic boarding school teachers) in the struggle for independence was not much heard in the academic landscape in this country. The important role of kiai pesantren to fight for independence, as well as to spread the idea of nationalism, has not been published comprehensively. Research publications on pesantren, so far, only appear in communal, political, and dynamic aspects in the country. The narrative is built by some researchers, that traditional-faced pesantren has a unique subculture with rich cultural treasures. Meanwhile, the role of pesantren in the struggle for independence, only faintly heard. The values of the nationality and heroism of the kiai pesantren still need to be explored in depth. Kiai Bisri Mustofa is an important figure in the narrative of the struggle for Indonesian independence. This figure often reviewed as a lecturer, writer, and pesantren’s caretaker. His work in the struggle for independence, as well as his ideas in the framework of nationality need to be explored as a spirit of struggle. This article focuses on the following questions: What is the principle of Kiai Bisri Mustofa’s national struggle? What are Kiai Bisri Mustofa’s ideas about nationalism and patriotism in his books? What can we learn from the national struggle shown by Kiai Bisri Mustafa? By reviewing the biography of the struggle and interpreting the series of ideas in Al-Ibriz series, we can perceive the configuration of Kiai Bisri Mustofa’s ideas about the struggle for independence. Keywords: Kiai Bisri Mustofa, pesantren, the struggle for independence, nationality, nationalism